Root pattern: shooting in the dark? - Dolan, L; Scheres, B (1998)
Root pattern formation takes place in the embryo and is propagated through subsequent growth and development of the seedling root meristem. Pattern is maintained by positional cues and in some cases by local cell interactions. Such interactions are involved in the balance between cell division and differentiation in cells neighbouring the quiescent centre. This balancing act also occurs in the shoot in which the genetic circuitry underpinning this phenomenon has been characterised. The common genetic mechanism of patterned cell differentiation in the epidermis between the root and shoot extends these parallels further. Given that these shared mechanisms exist, it is tempting to speculate that they reflect the fact that roots may be derived, shoot structures. Alternatively such mechanisms may reflect an evolutionary convergence of genetic mechanism.